Isolated fallopian tube torsion with partial hydrosalpinx in a premenarcheal girl: a case report - Višnjić, Stjepan (BioMed Central, 2014)
INTRODUCTION: Isolated fallopian tube torsion as a complication of a preexisting hydrosalpinx is a rare finding in pediatric patients. The obvious rarity of this condition, its subtle diagnostic features and dissonant previous reporting about the appropriate therapeutic approach according to age, future conception capacity and potential complications of possible pregnancies make the decision about which surgical approach to use very difficult. In this report, we describe the case of a patient with such a presentation and review the literature. Very few similar reports of neosalpingostomy in pediatric patients have been published to date. CASE PRESENTATION: In our present report, we describe the case of an 11-year-old Caucasian prepubertal girl who presented to our hospital with complaints of abdominal pain in the right lower quadrant, nausea and vomiting. The diagnostic workup led us to conclude that she had a torsion of the right ovary, which was cystically altered. Exploratory surgery revealed a partial hydrosalpinx and consecutive isolated torsion of the fimbrial part. The proximal isthmic part of the fallopian tube was intact and vital. Restorative surgery was performed to create a neosalpingostomy on the viable isthmic part of the tube and remove the cystic and twisted fimbrial and infundibular parts. CONCLUSION: The surgical procedure described in this report is technically simple and feasible, but leaves doubts about the final outcome.